MANAJEMEN BERBASIS SEKOLAH DALAM MENGEMBANGKAN DAN MEWUJUDKAN BUDAYA MUTU DALAMPENDIDIKAN SAINS - Zuhdan K. Prasetyo; Slamet Slamet (Jurnal Cakrawala Pendidikan, 2003)
The centralization and bureaucratic climate in the planning andprocessof national education management, which has been appliedso far, cannot be maintained anymore to answer the effortofrealizing the civil democracy. Democracy in the educational processhas broughtto it an implication of planning a decentralizededucational management, whichis felt to fulfill community morethan govemment needs.By optimizing the role of decentralizationin education and especially by implementing the school-basedmanagementas something creative formulated in a regionalautonomy form, a quality culture must become a priority.It isbecause in the globalization era Indonesians mustbe able to face thechallenges and demandsin the future which get increasingly harderand harder. Weare demanded to be not only a more developedcountry but also a more independent one and such a condition canbe usedas the foundation for the achievement of a prosperouscommunity based onPancasila and UUD 1945.The school-based management is hoped to be able to change themediocre culture which has been adopted into the quality culture inthe processof the educational management in facing theglobalization era.In science education the contribution that can begivento such a change in culture must be in process skills behaviors. beliefs. values, and attitudes that always keep Indonesiansin high quality condition. To keep the culture in its qualifiedcondition, total quality management can be used.In related to PP No. 22 Tahun 1999 about regional autonomy,the implementationof the integrated quality management isaccomplishedby using the school-based management system. It isclear that the etIortto realize the qualified management in scienceeducation canbe held. The regional autonomy and that kind ofmanagement convince us that all decisions or policies in theorganizationof education must be taken based on a standard qualitythroughout the roleof the teacher, parents, society, supervisor, anduniversity. Some standards that functionas the watch-dogs of thequalityof our national education must not merely be aimed at thecompetenceof the student but also at the teaching and educationalassessment standardsin science education